Weight gain of HIV-exposed, uninfected children born before and after introduction of the 'Option B+' programme in Malawi. (24th September 2018) - Msukwa, Malango T.; Estill, Janne; Haas, Andreas D.; van Oosterhout, Joep J.; Tenthani, Lyson; Davies, Mary-Ann; Tal, Kali; Phiri, Nozgechi; Spoerri, Adrian; Mthiko, Bryan C.; Chimbwandira, Frank; Keiser, Olivia
Abstract : Objective: To compare birth weight and weight gain in HIV-exposed, uninfected (HEU) infants up to 24 months old, who enrolled in the Malawian national HIV care clinic (HCC) programme either before or after Option B+ (OB+) was implemented. Design, setting and participants: HIV-exposed infants enrol in the HCC programme as soon as possible after birth and are followed up to at least 24 months old. This analysis includes HEU infants with recorded birth weight, date of birth, gender and at least one follow-up weight measurement from 21 health facilities in central and southern Malawi (January 2010–December 2014). Weight-for-age z scores (WAZ) were derived and compared by birth period using linear regression at birth and mixed effects models for postnatal weight gain up to 24 months old. Results: Of 6845 HEU infants included in this study, 88.5% were born after OB+. The proportion of infants exposed in utero to combination antiretroviral therapy (ART) significantly increased after OB+ was implemented, and infants were exposed to ART for a longer time. There was no significant difference in WAZ at birth ( P = 0.654) among HEU infants by birth period, but postnatal weight gain was faster among HEU infants born in the Option B+ period than infants born pre-Option B+. Conclusion: Birth weight was not affected by longer exposure to ART during pregnancy after OB+ was introduced, when weight gain in HEU infants was faster, possibly because their mothers were in better health. Abstract : Supplemental Digital Content is available in the text